2021
DOI: 10.1108/sbr-02-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

Gauging the ethical sensitivity of accounting students: the effect of money attitudes

Abstract: Purpose This paper aims to examine the attitude of accounting students towards money and their ethical perceptions, and ascertains whether ethical perception of students could be influenced by their attitudes towards money. Design/methodology/approach A survey method of research was adopted, and a set of questionnaires based on the money ethic scale (MES) and existing ethical scenarios was administered to the target respondents. The MES was subjected to an exploratory factor analysis to examine its dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Females were found to be more careful with their money as their scores on the factor budget were significantly higher than of males (Tang, 1992; Owusu et al ., 2021). Scores on the factors – good, achievement and freedom (power) were found to be more for men than women, though the correlations were not significant.…”
Section: Gender and Money Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…Females were found to be more careful with their money as their scores on the factor budget were significantly higher than of males (Tang, 1992; Owusu et al ., 2021). Scores on the factors – good, achievement and freedom (power) were found to be more for men than women, though the correlations were not significant.…”
Section: Gender and Money Attitudesmentioning
confidence: 99%
“…(2005) found that men scored significantly higher than women on factors – achievement, respect and power, while women scored higher on the factor budget than men, though the results on this factor were not found to be significant. Owusu et al . (2021) also found that mean scores of men on the factor respect was higher than that of women.…”
Section: Gender and Money Attitudesmentioning
confidence: 99%
“…Ethical issues arise due to the challenging position of tax consultants who struggle to serve two masters, namely the taxpayer as their client and the government as their principal (Yustina & Hertiningtyas, 2021;Mangoting et al, 2019). In practice, it is not easy for individuals to make ethical decisions as it heavily depends on their ability to identify ethical dilemmas and evaluate them in specific situations (Owusu et al, 2021;Dunn & Sainty, 2019). Attitude plays a central role in discussing individual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the occurrence of scandals (Worldcom, Satyam, Adelphia Communications, Enron, Anderson etc.) which were attributable primarily to weak corporate ethics and corporate governance risks such as conflicts of interest, lucrative compensation and other issues emanating from the agency relationship (Arjoon, 2006; Owusu et al , 2021). Relatedly, corporate governance and disclosure research has increased in various jurisdictions (Hermalin and Weisbach, 2012; Matuszak et al ., 2019; Pinto et al ., 2019) as a way to promote effective governance and ensure that organizations fulfill their objectives while prioritizing stakeholder interests.…”
Section: Introductionmentioning
confidence: 99%